Managerial performance measures in management accounting practices of Malaysian institutions of higher learning / Zubir Azhar and Ibrahim Kamal Abdul Rahman - Azhar, Zubir (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
While attention has been paid to other industries exhibiting effective use of management accounting practices (MAPs) and performance measurement systems, Malaysian service industry in general and education sector in particular have received less. At its inception, this research examines the performance of Institutions of Higher Learning (IHLs) in providing management accounting functions by way of looking at the relationship between the application of management accounting techniques (MATs) and the performance of managerial activities of IHLs. This takes into account the ramifications on two different sets of techniques used, i.e., traditional MATs (TMATs) and advanced MATs (AMATs). This study also identifies the relevant key performance indicators (KPIs) of IHLs as to determine the best practiced measures for tertiary institutions within the Malaysian context. Data are drawn from a survey among finance offices of both public and private IHLs of 32 responses. Findings indicate the use of performance measurement by in institutions of higher learning (IHLs) is pervasive, although survey respondents are less enthusiastic about measurement effectiveness. Study results show subtle distinctions between public IHLs and private IHLs in their use of performance measurements for management accounting functions. Research findings further indicate the eagerness of Malaysian IHLs in using KPIs as one of their MATs in order to obtain the benefits of best management accounting practices.